2016
DOI: 10.3758/s13428-016-0728-y
|View full text |Cite
|
Sign up to set email alerts
|

Can Lextale-Esp discriminate between groups of highly proficient Catalan–Spanish bilinguals with different language dominances?

Abstract: Researchers have recently introduced various LexTALE-type word recognition tests in order to assess vocabulary size in a second language (L2) mastered by participants. These tests correlate well with other measures of language proficiency in unbalanced bilinguals whose second language ability is well below the level of their native language. In the present study, we investigated whether LexTALE-type tests also discriminate at the high end of the proficiency range. In several regions of Spain, people speak both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Similarly, the correlations between the different tests in each language showed that despite the underlying common aim, the indices provided are complementary and that the additional information provided by each of them is necessary. In line with previous research, some tests correlated quite highly (e.g., Ferré and Brysbaert, 2016), but it is worth noting that none of the correlations were close to ceiling. Furthermore, correlations between self-ratings and some of the objective tests were relatively low, suggesting that self-ratings alone are not an optimal reflection of proficiency (cf.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, the correlations between the different tests in each language showed that despite the underlying common aim, the indices provided are complementary and that the additional information provided by each of them is necessary. In line with previous research, some tests correlated quite highly (e.g., Ferré and Brysbaert, 2016), but it is worth noting that none of the correlations were close to ceiling. Furthermore, correlations between self-ratings and some of the objective tests were relatively low, suggesting that self-ratings alone are not an optimal reflection of proficiency (cf.…”
Section: Resultssupporting
confidence: 90%
“…It has been judged to give a good indication of overall proficiency. Moreover, because results are not at ceiling level for first language users, it can be used for the assessment of highly proficient first and second language users (Ferré & Brysbaert, 2017). Lemhöfer and Broersma (2012)…”
Section: Results Studymentioning
confidence: 99%
“…A first limitation is that our lists are based on yes/no word decision. Although this test has been validated several times (Ferré & Brysbaert, 2017;Harrington, & Carey, 2009;Lemhöfer & Broersma, 2012;Meara, & Buxton, 1987;Zhang et al, 2019), it remains true that it does not measure word knowledge in great depth. Participants may know that a letter sequence is an English word, without much knowledge about the meaning of the word, let alone the various senses and unrelated meanings English words may have.…”
Section: Discussionmentioning
confidence: 99%